PENGARUH PROFITABILITAS, LIKUIDITAS, LEVERAGE DAN PERTUMBUHAN PENJUALAN TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2014-2016 - Isna Aulia Dewi, 14.05.52.0257; Srimindarti, Ceacilia (Students' Journal of Accounting and Banking, 2018)
This study aims to examine and analyze the effects of Profitability, Liqudity, Leverage and Sales Growth of Financial Distress on Manufacturing Companies Listed on BEI Period 2014-2016. The population in this study is all Manufacturing Companies Registered in BEI Period 2014-2016. The sample selection using purposive sampling method. The analysis tool used in this research is logistic regression analysis. The results of the research show that Profitability and Leverage influence has Positive significant of financial distress while Liquidity have positive not significant effect on financial distress and Sales Growth have negative not significant effect on financial distress. Keywords: Financial Distress, Profitability, Liquidity, Leverage and Sales Growth.